The Invention of the Beautiful Game : Football and the Making of Modern Brazil - Bocketti, Gregg (Book collections on Project MUSE., 2016)
"In this cross-cutting cultural history, Gregg Bocketti traces the origins of soccer in Brazil from its elitist, Eurocentric identity as 'foot-ball' at the end of the nineteenth century to its subsequent mythologization as the specifically Brazilian 'futebol, ' o jogo bonito (the beautiful game), in the twentieth century and beyond"--Provided by publisher